Fretting-fatigue induced failure of a connecting rod. (February 2019) - Chao, J.
Abstract: This paper analyses the failure of an oblique split connecting rod with serrated joint faces in a medium-speed gas engine at a cogeneration plant. Engine failure occurred suddenly after 20, 000 h of service by malfunctioning without the engine control system providing an automatic engine shutdown signal. The failure affected two trains, which were mounted on the same crankpin and to the crankshaft itself. The analysis was concentrated on the connecting rod in which fatigue features on the fracture surface were observed. The location of the fracture in this connecting rod occurred close to the lower joint within the vicinity of the connecting rod axis. Beach marks on the fracture surfaces indicated that the crack initiated from the big end internal surface, approximately 5 mm from the oil groove, away from any geometric stress concentration. To determine the fracture cause, a material characterization and an analysis of the material state near the fracture initiation point was conducted. The analysis was extended to the bearing shells of the damaged trains and to the bearing shells of a connecting rod that did not fail. The results suggest that the mechanism of failure of the engine may have probably been fretting-fatigue produced by the relative micro-movements between the bearing back and the housing bore. Highlights: Engine failure was fretting induced in the big end internal surface. Fretting occurred between the contact surfaces of the bearing shell and the housing. Fretting damage encouraged the press-fit loosening and further fretting fatigue. A critical crack size initiated away from any geometric stress concentration. The crack extended via mechanical fatigue until failure occurred.